Factors That Related the Academic Procrastination of New Students in Learning with the Blended Learning - Diwa Agus Sudrajat; Putri Oktavia Hasim; Tria Firza Kumala; Eva Supriatin; Suci Noor Hayati (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aims: Academic procrastination will harm student academic achievement. Based on the research results at nursing school in West Java, second-level students showed high academic procrastination behavior (Utami, 2021), and the effects of interviews with a lecturer showed that about 20% of new students did academic procrastination. So, research is needed on the factors that affect academic procrastination in students. Objective: This study aims to determine the factors that related the academic procrastination of new students in learning with blended learning. Methods: This study uses a quantitative descriptive: a cross-sectional study, the respondents are a convenience sampling of 167 new students, data collection by questionnaire. Analysis of the data used in this study is the Pearson Correlation Moment, Mann-Whitney Test, Spearman Rank Correlation, Point-biseral correlation, and linear regression. Results: Academic procrastination behavior tends to be high, self-efficacy tends to be low, and self-control is moderate (70.8%). The most influential factors in the academic procrastination of new students are gender, self-efficacy, and self-control, which are significantly related to -Value 0.00. Conclusion: Male gender and self-control are the most influential factors in academic procrastination. Suggestion: For academics, they can maximize the SCL (Student Centered Learning) learning method with Blended learning, and for students, especially boys, they must increase their activeness and independence in learning so that it is expected to increase self-efficacy and self-control.